2015
DOI: 10.3892/mmr.2015.4498
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of hFOB1.19 osteoblast cells on TGF-β1-SF-CS three-dimensional scaffolds

Abstract: The aim of the present study was to examine the biocompatibility of transforming growth factor-β1-silk fibroin-chitosan (TGF-β1-SF-CS) scaffolds. In order to provide an ideal scaffold for use in bone tissue engineering, TGF-β1 was introduced into the SF-CS scaffold in order to reconstruct a three dimensional scaffold, following which hFOB1.19 osteoblast cells were seeded onto TGF-β1-SF-CS and SF-CS scaffolds. On the TGF-β1-SF-CS and SF-CS scaffolds, the cell adhesion rate increased in a time-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It was necessary to estimate the toxicity of the obtained SeB-NPs and Ag SeB-NPs for further tissue engineering applications. Osteoblasts were commonly used to evaluate the cytocompatibility of nanoparticles and/or scaffold in tissue engineering 58,59 . In this study, the cytocompatibility of SeB-NPs and Ag SeB-NPs was assessed by culturing with hFOB 1.19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was necessary to estimate the toxicity of the obtained SeB-NPs and Ag SeB-NPs for further tissue engineering applications. Osteoblasts were commonly used to evaluate the cytocompatibility of nanoparticles and/or scaffold in tissue engineering 58,59 . In this study, the cytocompatibility of SeB-NPs and Ag SeB-NPs was assessed by culturing with hFOB 1.19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…On day 21 after the start of osteogenic induction, the cells were fixed with 4% paraformaldehyde. Calcium nodules were stained with 0.2% alizarin red and observed using a microscope(CKX41, Olympus, Tokyo, Japan) 26) .…”
Section: Preparation and Identifi Cation Of Bmscsmentioning
confidence: 99%
“…In vitro, it has been proved that HAOBs have stronger osteogenic capability than marrow stromal stem cells [15]. In the current study, HOABs were successfully cultured as previously reported [16, 17] and functions of BBR in HAOB proliferation and osteogenic differentiation were investigated.…”
Section: Discussionmentioning
confidence: 69%